Are vaccines a potential treatment for long covid?. (18th May 2022) - Sivan, Manoj; Greenhalgh, Trisha; Milne, Ruairidh; Delaney, Brendan
Abstract : Benefits are possible, but we need more evidence and a mechanism of action